COVID-19 anxiety among undergraduate students of a medical college in Chengalpattu district – A cross-sectional study - Abhilash Bagavanantham Adiththan; Muthileswaran Muniyasamy; Dinesh Kumar Ganesan; Raja Tharumaraj Kottayan; Vishalini Anbuselvan; Buvnesh Kumar Mohan Kumar (Asian Journal of Medical Sciences, 2023)
Background: COVID-19 is caused by severe acute respiratory syndromes-CoV-2, a virus that affects the physical as well as mental health of people. Aims and Objectives: Our study was conducted to estimate the COVID-19 anxiety prevalence and its associated sociodemographic factors in a medical college. Materials and Methods: Undergraduate medical students of a medical college in Chengalpattu district were the study participants, with inclusion criteria of students above 18 years of age from 2nd, 3rd, and final year and interns being included for the study. Using simple random sampling, students were selected with a sample size of 197. After obtaining approval from the Institutional Human Ethics Committee and informed consent, data were collected using a structured and pre-tested questionnaire, with anxiety being assessed using coronavirus anxiety scale and data analyzed using SPSS version 21. The statistical tests used were proportions, Chi-square test. P<0.05 was considered to be statistically significant. Results: Among the 197 students, males constituted 82 (41.6%) and females 115 (58.4%), of which 60 (73.1%) of males and 88 (76.5%) of females had COVID-19 anxiety. Overall 75.1% had COVID-19 anxiety. Based on the year of study, 43 (22%) 2nd-year students and 38 (19.3%) 3rd-year students, 29 (14.8%) final-year students, and 38 (19.3%) inters had COVID-19 anxiety. Sociodemographic factors such as the type of family, year of study, and staying with parents had a strong association with COVID-19 anxiety. Conclusion: In our study, 75.1% experience Coronavirus related anxiety, and thus, there is need for focus on the mental well-being of undergraduate students requiring attention as well as support from college administration, family, and society to cope up with the pandemic situation.